2022
DOI: 10.1177/10781552221122026
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with nausea and vomiting in children with cancer receiving chemotherapy

Abstract: Introduction Despite treatment with antiemetic medications, nausea remains uncontrolled for many children receiving chemotherapy. One reason is that risk factors for nausea in children remain poorly explored. The purpose of this study was to identify risk factors for chemotherapy-induced nausea (CIN) in children. Methods Prospective, observational study including 101 children (median age 6.4 years, range 0.8–17.9) with cancer receiving moderately or highly emetogenic chemotherapy. Primary endpoints were comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
0
4
1
Order By: Relevance
“…Unlike what is seen in adults, no gender-based differences in the perception of CINV were identified [8,10]. Disease-specific analyses showed that children with hematological malignancies are more likely to experience delayed CINV compared to those with solid tumors, likely due to the variable use of steroids in this population in the actual treatment [8]. Multi-day chemotherapy protocols commonly used in children lead to longer acute-phase duration, which has been associated with poorer acute-phase CIV control, likely due to the overlap of different phases [3].…”
Section: Risk Factors For Cinv Among Childrencontrasting
confidence: 66%
See 2 more Smart Citations
“…Unlike what is seen in adults, no gender-based differences in the perception of CINV were identified [8,10]. Disease-specific analyses showed that children with hematological malignancies are more likely to experience delayed CINV compared to those with solid tumors, likely due to the variable use of steroids in this population in the actual treatment [8]. Multi-day chemotherapy protocols commonly used in children lead to longer acute-phase duration, which has been associated with poorer acute-phase CIV control, likely due to the overlap of different phases [3].…”
Section: Risk Factors For Cinv Among Childrencontrasting
confidence: 66%
“…Among children, older age and susceptibility to motion sickness have been consistently identified as risk factors for acute CINV [7][8][9]. Unlike what is seen in adults, no gender-based differences in the perception of CINV were identified [8,10]. Disease-specific analyses showed that children with hematological malignancies are more likely to experience delayed CINV compared to those with solid tumors, likely due to the variable use of steroids in this population in the actual treatment [8].…”
Section: Risk Factors For Cinv Among Childrenmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6][7][8] Based on the incidence of vomiting caused by chemotherapy drugs, it is classified into 4 risk levels: high (≥90%), moderate (30-90%), low (10-30%), and minimal (<10%). [9,10] Given the intricate pathogenesis of CINV and significant inter-individual variations among patients, [11] a combination of drugs should be administered as a prophylactic measure against vomiting in patients undergoing moderate or highly emetic chemotherapy (MEC/HEC). [9,10,[12][13][14][15][16][17][18][19][20] The commonly used antiemetic drugs in clinics mainly include 5-HT 3 receptor antagonists (5-HT 3 RA), neurokinin-1 antagonists (NK-1 RA), glucocorticoids, dopamine receptor antagonists, and certain psychotropic drugs .…”
Section: Introductionmentioning
confidence: 99%
“…The therapy works by adding dexamethasone for moderate emetogenic chemotherapy (MEC) for anti-emetic supportive care and, for highly emetogenic chemotherapy (HEC), adding of the NK 1 receptor antagonist, aprepitant, to this therapy. 2,3 This comment focuses on the risk factors for CIN in children which were studied by Eliasen et al 4 In their recent report in Journal of Oncology Pharmacy Practice, Eliasen et al found that susceptibility to motion sickness and age can influence the risk of acute CIN. Although the clinical relevance of Eliansen's study is clear, some methodological issues can be raised concerning the use of statistical modelling, and the choices made on the inclusion of risk factors in the analyses and the final conclusions.…”
mentioning
confidence: 99%